Evaluation of diuretic and laxative activity of aqueous extract of Argemone mexicana leaves in rats - Shripad Motilal, Bairagi; Pathan, Inayat P.; Nitin, Nema (Ars Pharmaceutica (Internet), 2017)
Objectives: Argemone mexicana have been widely studied for its several pharmacological benefits and has been used in traditional medicine to treat constipation like symptoms. The present study carried out to evaluate the extract for its diuretic and laxative potential. Method: The aqueous extract of Argemone mexicana prepared using percolation method and subjected to phytochemical analysis. Evaluation of diuretic and laxative activity was carried out using metabolic cage apparatus and flame photometer as per the standard method reported earlier. Frusemide (20 mg/kg) and sodium picosulate (5 mg/kg) were served as positive control for diuretic activity and laxative activity respectively. Result: The extract showed significant diuretic activity at 250 mg/kg dose when compared to standard frusemide. Even this extract also effective in increasing electrolyte concentration. Whereas the extract at 250 mg/kg showed significantly increasing in fecal output, and also significantly increased the weight of feces at 100 mg/kg and 200 mg/kg dose. Conclusion: The previous significant finding supports the traditional use of Argemone mexicana for its diuretic and laxative potential